The Dissolution of Political Parties as Sanctions for Corruption Crimes - Alwi Yusup Ramadhan; Muhammad Dzikri; Irsyad Ilyas; Yuliant Prajaghupta (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2023)
Corporate criminal responsibility in corruption and money laundering committed by political parties as corporations. This corruption crime stems from political parties committed by their members. However, in practice, it is difficult to identify the actions of members of political parties as actions that can be accounted for by political parties. The main problem in this study is the sanction of dissolution of political parties as corporations that have been proven to commit criminal acts of corruption and money laundering as a form of criminal responsibility from political parties. The research method used in this study is a statutory, analytical, and conceptual approach. The legal materials in this study come from secondary data, including primary, secondary, and tertiary legal materials. Based on the results of this study, it can be seen that the Constitutional Court can only carry out the dissolution of a political party as a corporation. The decision of the District Court Judge that was handed down was used as a reference for the application by the government through the attorney general and/or the Minister whom the President had appointed to submit a request for its dissolution to the constitutional court. The execution of the dissolution is in the hands of the Constitutional Court according to its authority. Pertanggungjawaban pidana korporasi dalam tindak pidana korupsi dan pencucian uang yang dilakukan oleh partai politik sebagai korporasi. Tindak pidana korupsi ini berasal dari partai politik yang dilakukan oleh anggotanya. Akan tetapi dalam prakteknya sulit mengidentifikasi perbuatan anggota partai politik menjadi perbuatan yang dapat dipertanggungjawabkan kepada partai politik. Pokok permasalahan dalam penelitian ini adalah sanksi pembubaran partai politik sebagai korporasi yang telah terbukti melakukan tindak pidana korupsi dan pencucian uang sebagai bentuk pertanggungjawaban pidana dari partai politik.Metode penelitian yang digunakan dalam penelitian ini adalah melalui pendekatan perundang-undangan (Statue Aproach), pendekatan analisis (Analytical Approach), pendekatan konseptual (Conceptual Approach), Sumber bahan hukum yang terdapat dalam penelitian ini berasal dari data sekunder yang mencakup bahan hukum primer, sekunder, dan tersier. Berdasarkan hasil penelitian ini dapat diketahui bahwasannya Pembubaran partai politik sebagai korporasi hanya dapat dilakukan oleh Mahkamah Konstitusi. Putusan Hakim Pengadilan Negeri yang dijatuhkan hanya dijadikan acuan permohonan oleh pemerintah melalui jaksa agung dan/atau Menteri yang telah ditunjuk oleh presiden untuk memberikan permohonan pembubarannya kepada mahkamah konstitusi. Pelaksanaan eksekusi pembubaran ada ditangan Mahkamah Konstitusi sesuai kewenangan yang dimiliki.